2012
DOI: 10.1002/bdra.23033
|View full text |Cite
|
Sign up to set email alerts
|

Emerging data on the use of anti‐tumor necrosis factor‐alpha medications in pregnancy

Abstract: Anti-tumor necrosis factor (TNF) α medications are used for the treatment of a number of autoimmune diseases. Evaluation of pregnancy safety for these medications is complicated by the contribution of the underlying maternal disease to adverse pregnancy outcomes, such as preterm delivery and reduced birth weight. Placental transport of these medications is thought to be minimal in the first trimester, thereby providing some reassurance regarding theoretical risks for congenital malformations. Available human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 60 publications
0
42
0
1
Order By: Relevance
“…Immunoglobulin G (IgG) is the only major class of antibody that is transported across the human placenta. Fetal levels of IgG in umbilical venous blood are low in the first two trimesters of pregnancy and do not surpass maternal levels of IgG until the beginning of the third trimester when active transport of the IgG molecules across the placenta increases rapidly (Chambers and Johnson, 2012). Transport of IgG is facilitated by the neonatal Fc receptor (FcRn) on the placenta.…”
Section: Fetal Exposure To Biologic Agents During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoglobulin G (IgG) is the only major class of antibody that is transported across the human placenta. Fetal levels of IgG in umbilical venous blood are low in the first two trimesters of pregnancy and do not surpass maternal levels of IgG until the beginning of the third trimester when active transport of the IgG molecules across the placenta increases rapidly (Chambers and Johnson, 2012). Transport of IgG is facilitated by the neonatal Fc receptor (FcRn) on the placenta.…”
Section: Fetal Exposure To Biologic Agents During Pregnancymentioning
confidence: 99%
“…One case report of a death due to disseminated Bacillus Calmette-Guérin (BCG) infection following live BCG vaccination in an infant borne to a mother receiving infliximab during pregnancy, caused significant and warranted alarm (Cheent et al, 2010). Multiple studies have documented that levels of anti-TNF agents are detected in infants at birth and decline thereafter (Chambers and Johnson, 2012); however, a few studies noted that drug clearance could take up to 1 year after birth (Julsgaard et al, 2016). Infliximab clears more slowly than adalimumab (Julsgaard et al, 2016).…”
Section: Fetal Exposure To Biologic Agents During Pregnancymentioning
confidence: 99%
“…57 The use of TNF-α inhibitors in pregnancy remains controversial, and biologic medications should only be used only if benefit greatly outweighs the risks and all other A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 16 treatment options have been exhausted. 76 Surgical therapy is considered as a last resort for cases of extensive or refractory disease.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…All the anti-TNF agents are currently classified as pregnancy category B (no fetal harm in animal studies, but inadequate studies in pregnant women). Numerous pregnancies inadvertently occurring while on these agents during the first trimester have been reported [104], and there has not been an increased risk of congenital malformations reported with the use of either infliximab or adalimumab during pregnancy [105]. Also, case reports have shown that children who were breastfed during maternal treatment with TNF inhibitors had normal growth and development [106].…”
Section: Adalimumabmentioning
confidence: 99%